Continuity of care in mental health: understanding and measuring a complex phenomenon. - Burns, T; Catty, J; White, S; Clement, S; Ellis, G; Jones, I; Lissouba, P; McLaren, S; Rose, D; Wykes, T (2009)
BACKGROUND: Continuity of care is considered by patients and clinicians an essential feature of good quality care in long-term disorders, yet there is general agreement that it is a complex concept. Most policies emphasize it and encourage systems to promote it. Despite this, there is no accepted definition or measure against which to test policies or interventions designed to improve continuity. We aimed to operationalize a multi-axial model of continuity of care and to use factor analysis to determine its validity for severe mental illness. METHOD: A multi-axial model of continuity of care comprising eight facets was operationalized for quantitative data collection from mental health service users using 32 variables. Of these variables, 22 were subsequently entered into a factor analysis as independent components, using data from a clinical population considered to require long-term consistent care. RESULTS: Factor analysis produced seven independent continuity factors accounting for 62.5% of the total variance. These factors, Experience and Relationship, Regularity, Meeting Needs, Consolidation, Managed Transitions, Care Coordination and Supported Living, were close but not identical to the original theoretical model. CONCLUSIONS: We confirmed that continuity of care is multi-factorial. Our seven factors are intuitively meaningful and appear to work in mental health. These factors should be used as a starting-point in research into the determinants and outcomes of continuity of care in long-term disorders.